Clinical Edema and Chest X-Ray Findings in Acute Poststreptococcal Glomerulonephritis - Husein Albar; Syarifuddin Rauf; Dasril Daud; Azis Tanra; M. Faried Kaspan (Paediatrica Indonesiana, 1997)
We report the results of a retrospective study evaluating clinical edema and chest X-ray findings in 17b patients with acute poststreptococcal glomeruÂ¬lonephritis (APSGN), hospitalized in the Pediatric Nephrology Unit of Ujung Pandang General Hospital, from January 1, 1980 through December 31, 1990. Of the total 194 patients, only 176 fulfilled the criteria and could be evaluated. There were 98 boys (55,7%) and 78 girls (44.3%) aged between 1 year 9 months and 14 years, mostly beÂ¬tween 6-12 years (72.8%). We found that edema of the palpebra was more frequently noted (98.9%) than that of the pretibia (71.6%), face (64.2%) and ascites (21.0%). This study showed evidence of cardiomegaly (84.1%), pulmonary vascular congestion (68.2%), pleural effusion (65.9%) and pulmonary' edema (48.9%). Our study results documented that roentgenographic abnormality of the chest of patients with APSGN, included each of the following findings, e.g., cardiomegaly, pleural effusion, pulmonary vascular congestion, and pulmonary edema, was significantly more frequent in patients with clinical evidence of severe edema than those with moderate and mild edema (p < 0.01).